Stony coral tissue loss disease: a review of emergence, impacts, etiology, diagnostics, and intervention - Erin Papke; Ashley Carreiro; Caroline Dennison; Jessica M. Deutsch; Lys M. Isma; Sonora S. Meiling; Ashley M. Rossin; Andrew C. Baker; Marilyn E. Brandt; Neha Garg; Daniel M. Holstein; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2024)
Stony coral tissue loss disease (SCTLD) is destructive and poses a significant threat to Caribbean coral reef ecosystems. Characterized by the acute loss of coral tissue, SCTLD has impacted over 22 stony coral species across the Caribbean region, leading to visible declines in reef health. Based on the duration, lethality, host range, and spread of this disease, SCTLD is considered the most devastating coral disease outbreak ever recorded. Researchers are actively investigating the cause and transmission of SCTLD, but the exact mechanisms, triggers, and etiological agent(s) remain elusive. If left unchecked, SCTLD could have profound implications for the health and resilience of coral reefs worldwide. To summarize what is known about this disease and identify potential knowledge gaps, this review provides a holistic overview of SCTLD research, including species susceptibility, disease transmission, ecological impacts, etiology, diagnostic tools, host defense mechanisms, and treatments. Additionally, future research avenues are highlighted, which are also relevant for other coral diseases. As SCTLD continues to spread, collaborative efforts are necessary to develop effective strategies for mitigating its impacts on critical coral reef ecosystems. These collaborative efforts need to include researchers from diverse backgrounds and underrepresented groups to provide additional perspectives for a disease that requires creative and urgent solutions.